Computer-Assisted Porcelain Laminate Veneer Preparation: A Scoping Review of Stereolithographic Template Design and Fabrication Workflows - Xin Guan; Yew Hin Beh; In Meei Tew (MDPI AG, 2024)
Computer-assisted preparation of porcelain laminate veneers (PLVs) using stereolithographic templates has been developed to enhance the accuracy of tooth preparation. However, the digital workflows involved in guided PLV preparation remain inconsistently defined across various practices. Therefore, this scoping review aimed to examine publications on computer-assisted PLV preparation to identify the key stage of digital workflows involved in designing and fabricating stereolithographic templates, as well as to highlight the limitations of various template designs. This scoping review aimed to identify publications on digital workflows for designing and fabricating stereolithographic templates in computer-assisted porcelain laminate veneer preparation. A systematic search on MEDLINE/PubMed, Web of Science and Scopus identified English-language articles published from 2014 to March 2024. Eligible articles focused on digitally designed and fabricated tooth reduction templates for porcelain laminate veneers, excluding conventional tooth preparation procedures for tooth reduction assessment. Seven clinical reports were included, demonstrating various 3D data acquisition techniques for virtual patient generation. All articles described virtual diagnostic wax-ups on digital casts, with two using a virtual articulator. Only five articles documented chair-side mock-ups with resin trial restorations to evaluate planned dental esthetics. Additionally, virtual tooth preparation prior to templates design was included in only four articles. The templates were designed using different software and ranged from simple designs with access windows to complex stacked templates with rotary instrument sleeved windows. Each template design had limitations affecting tooth reduction accuracy. All articles reported printing templates in clear acrylic resin using different technologies. In conclusion, the review highlights a lack of standardization in the digital workflow for designing stereolithographic templates for PLVs. Establishing a sound protocol for designing the tooth reduction templates is essential to ensure the accuracy and consistency of veneer preparation.